Analysis of Entrepreneurial Orientation and Innovation Strategies in Increasing Competitive Advantage (Empirical Study on Food Viral MSME Seblak in Sukabumi) - Andihilmi Al Sidiqin; Sopyan Al Saori; Resa Al Nurmala (Universitas KH. Abdul Chalim Mojokerto, 2025)
Economic development in Indonesia is growing very rapidly with micro, small and medium enterprises (MSMEs) and is one of the important pillars for the national economic sector. One of the rapidly growing MSMEs is the culinary sector in seblak MSMEs in Sukabumi City. Increased market competition among Seblak MSME players will affect the performance of the seblak MSME itself. To survive in the midst of market competition, seblak MSMEs must have a good strategy to maintain their business in competitive advantage. The purpose of this study was to determine the description and influence of entrepreneurial orientation and innovation strategies in increasing competitive advantage. The population in this study were 270 Seblak MSMEs in Sukabumi City registered at the One-Stop Investment and Integrated Services Office (DPMPTSP). The sample used amounted to 41 respondents, namely 15% of the population through purposive sampling. The method used is a quantitative method with an associative descriptive approach. The statistical results of the f test (simultaneously) there is a simultaneous and significant influence of the entrepreneurial orientation variable and innovation strategy on competitive advantage. Based on the results of the t test, entrepreneurial orientation has a positive effect on competitive advantage. And the results of testing innovation strategies have a positive effect on competitive advantage.